CORRUPTION IN CONTEMPORARY JAPANESE POLITICS (2001–2009) - Geležauskas, Andrius (Politologija, 2015)
Political corruption in Japan is a very important issue. According to the Global Corruption Barometer 2009 survey Japanese perceived political parties, public officials and civil servants to be the institutions which are the most affected by corruption. In addition, governmental measures against corruption are regarded to be ineffective and inadequate to the real situation. Japanese have keen concern toward Japanese political parties, intransparent activity of politicians and preventive measures taken by government. The purpose of this research is to examine political corruption phenomena in contemporary Japanese politics. Research questions are what are the structure, scale, and causes of political corruption in Japan during 2001–2009. For answering to these research questions first of all it is discussed the concept and definition of political corruption itself. Article overviews previous political corruption studies in Japan from the time of Second World War to the recent times, including the report of the Transparency International National Integrity System. In third chapter of article the scale, the varieties and the main practitioners of political corruption in Japan are to be analyzed. It reveals the biggest political corruption scandals in Japanese politics in given time-period. Last chapter focuses on the explanation of political corruption mechanism in Japan and in particular relationship with clientelism practises. Combination of primary and secondary sources led me to make the following conclusions on the main political corruption tendencies in Japan during 2001–2009. First, the Asahi Shimbun front page content analysis indicates that 2002 and 2007 are special years in the context of corruption studies because in those years published the largest number of political corruption articles and the biggest number of the new themes on the political corruption issue revealed. Second, the common point of the three most significant political corruption scandals during 2001–2009 is that all of them have the relationship with political finance issue and in particular a suspicion on the violation of the PFRL. This finding reaffirms the NIS statement that political finance is one of the top priority issues in Japanese corruption scheme. Third, illegal political donation and influence peddling are the most frequent types of corruption in Japan during the period of 2001–2009. Fourth, main practitioners of political corruption in Japan were the LDP members from the House of Representatives. In addition, in as many as nine cases the Diet member secretaries were involved in political corruption scandals. The Diet member secretaries play an important role in political corruption scheme because they are often responsible for the political fund management. Fifth, the most vulnerable institution to political corruption seems to be Ministry of Agriculture, Forestry and Fisheries and Ministry of Construction. Finally, article concludes that political corruption in Japan, to some extent, could be explained through the analysis of political clientelism.